Fear of Missing Out (FOMO) in Ready-to-Drink Coffee Consumption among Young People in Makassar - Siti Syarifah Wafiqah Wardah; Eureka Try Zarazwanty R. Laega; Zulfahmi Zulfahmi (Fakultas Ilmu Sosial dan Hukum, 2026)
This study aims to: (1) deeply understand the Fear of Missing Out (FOMO) phenomenon in ready-to-drink coffee consumption among young people in Makassar City, and (2) explore how FOMO shapes consumption behavior patterns in social contexts and social media use. The theoretical framework encompasses consumer behavior theory, FOMO in social psychology, and the influence of social media on purchasing decisions. This research employs a descriptive phenomenological qualitative approach through in-depth interviews with 16 informants aged 17–29 years in Makassar. Thematic analysis was applied. Results show: first, FOMO manifests as a real and significant phenomenon in ready-to-drink coffee consumption, expressed through curiosity toward viral products, impulse to follow trends, and fear of being left out of social experiences; second, FOMO shapes consumption patterns through three main mechanisms social media trends (Instagram and TikTok as amplifiers), peer group pressure, and the need for social identity and existence. The convenience of ready-to-drink format serves as a catalyst shortening the distance between FOMO-driven impulse and actual purchase. The novelty lies in qualitative exploration of FOMO in practical beverage consumption in Indonesian urban settings. Findings contribute to the theoretical understanding of FOMO as a consumer behavior determinant with practical implications for coffee businesses and policymakers.